Darned if you do [large type] - Ferris, Monica (Ferris, Monica. Needlecraft mystery, 2015)
After a tree falls on Tom Riordan's house and lands him in the hospital, the police discover a mountain of junk piled in his home. Locals in Excelsior, Minnesota -- including Betsy Devonshire and her Crewel World Monday Bunch -- offer to help clean up while Tom recuperates. Then Tom is found murdered in his hospital bed, and his cousin Valentina -- the sole heir to his property -- becomes the number one suspect. Betsy believes there's more to the case than meets the eye, but finding clues will be like looking for a needle in a haystack.